La conformité entre les règlements d'urbanisme, le plan d'urbanisme et le schéma d'aménagement - Marchand, François (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1986)
Since the adoption of an Act respecting land use and development, the council of a regional county municipality has a legal obligation to adopt a development plan. Every municipality in the regional county community is also required to adopt a planning program, a zoning by-law, a subdivision by-law and a building by-law. This program and those by-laws must be in conformity with the objectives of the development plan. In some cases, the local by-laws also must be in conformity with the local planning program. In the first part, this essay establishes the difference between the obligation of conformity with the regional plan and the obligation of conformity with the local planning program. In the second part, the essay analyses the principles of conformity ; first the principles of interpretation and second the principles of application.